SELF REGULATED LEARNING STRATEGY IN ELEMENTARY SCHOOL - Nuur Wachid Abdul Majid; Eliya Rochmah (Indonesian Journal of Education and Learning, 2018)
Elementary School is foundation of education in Indonesia that is very important to curve character and success in academic when they are be adult. Many factors that influence in the formation of characters and academics success of the students one of them is the ability of self-regulation or Self-Regulated Learning in learning activities in elementary school. Self-Regulated Learning has an important role in the implementation of teaching and learning process, especially in determining the success of teaching and learning process, because students who have this ability can manage and self-directed, able to adjust, and self-control, especially when facing difficulties in the learning process. This research is limited to a preliminary study covering three steps: (a) initial data and information collection; (b) planning; and (c) initial product development. By applying the learning strategy of SRL, students can arrange themselves in learning by involving the ability of cognition, metacognition, motivation, and active behavior as well as managed learning or in other words learning that rests on self-regulation.